Applications of image processing and soft computing systems in agriculture - Razmjooy, Navid; Estrela, Vania Vieira (A volume in the Advances in environmental engineering and green technologies (AEEGT) book series, 2019)
"This book examines the main uses of the shape analysis on some agricultural products, such as relationships between form and genetics, adaptation, product characteristics, and product sorting"--